Branding and Social Identity in Consumer Decisions and Retail Consumption in South Africa post covid-19 lockdown - Makhathini, Silindile Charmaine (University of the Witwatersrand, Johannesburg, 2023)
Consumer behavior continues to evolve, a phenomenon accentuated by various factors, notably the recent COVID-19 pandemic. Globally enforced lockdowns mandated by governments compelled individuals to seek new survival strategies, prompting shifts in their purchasing patterns. The restrictions on movement necessitated a surge in online shopping. Additionally, the pandemic fostered panic-driven bulk purchases, as consumers sought means of survival without adequate information on the duration of the crisis (Loxton et al., 2020)
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management Strategic Marketing - (MMSM) to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; SDG-8: Decent work and economic growth